The Regime's Violation of the Right to Property in the West Bank, Palestine: Rawabi Project as a Case Study - Osayd Awawda (The Constitutional Court of the Republic of Indonesia, 2020)
The purpose of this paper is to assess the Palestinian Constitutional Court's reasoning of its judgment in Rawabi Case, a case in which the Government's expropriation of a large area of privately-owned land was challenged before the Court. The expropriation was to transfer the ownership of that land to Bayti Real Estate Investment Company, a private company that later on built the first planned city in Palestine: Rawabi. This paper explains what implications the judgment in this case has on the relationship between the regime and other major private investors in the West Bank. The paper starts with explaining how some constitutional courts perform the function of providing credible commitments in the economic sphere, where such courts are situated in authoritarian settings. Then, it moves to the specific case of Rawabi, explaining the facts of the case and describing Rawabi's connections to the regime's interests. The paper concludes that the Constitutional Court has failed to perform its main function of upholding the Palestinian Basic Law and, in particular, protecting the right to property for the owners of the expropriated lands.